Analysis of a gas-liquid-liquid-solid catalytic reaction: kinetics and modeling of a semibatch slurry reactor - Roy, D.; Chaudhari, Raghunath V. (Industrial & Engineering Chemistry Research, 2005)
Hydrogenation of aniline to cyclohexylamine was studied in a gas-liquid-liquid-solid tetraphase system using cyclohexane and water as two immiscible liquid phases and ruthenium on alumina (2% Ru/Al2O3) as the catalyst. In addition to the higher catalytic activity with respect to the conventional three-phase system, the novel four-phase system was highly efficient in catalyst-product separation. Experimental data on concentration-time as well as hydrogen-consumption-time profiles were obtained to study the effect of concentration of aniline, catalyst loading, and the partial pressure of hydrogen. A detailed analysis of gas-liquid, liquid-liquid, liquid-solid, and intraparticle mass transfer was carried out using initial rate data to ensure the kinetic regime. On the basis of these data, several rate equations were evaluated to select a kinetic model. The kinetic parameters were estimated over a temperature range of 378-418 K by fitting the integral batch reactor data. A rate model considering adsorption of hydrogen on the catalyst surface followed by reaction with the liquid-phase components as the rate-limiting step was found to give the best fitting of the experimental concentration-time as well as the hydrogen-consumption-time data at different initial sets of reaction conditions. The activation energies, heat of adsorption, and entropy of adsorption were also evaluated.
Joint 5th International Symposium on Catalysis in Multiphase Reactors/4th International Symposium on Multifunctional Reactors, Portoroz-Portorose, SLOVENIA, JUN 15-18, 2005

Anchored Pd-complexes in mesoporous supports: synthesis, characterization and catalysis studies for carbonylation reactions - Sarkar, Bibhas R.; Chaudhari, Raghunath V. (Catalysis Today, 2012)
Pd(pyca)(PPh3)(OTs) [pyca = 2-picolinate] complex is efficiently anchored inside different mesoporous matrices, such as MCM-41, MCM-48, SBA-15 using a molecular aminopropyl tether moiety employing different synthesis strategies. Thorough characterization of the materials using powder XRD, multinuclear (C-13, Si-29, P-31) CP-MAS NMR, XPS, SEM, N-2-sorption studies etc. confirmed the successful anchoring of the palladium complex to the walls of the support matrices thus establishing the synthesis protocols unambiguously. The catalysts were found to be highly active and selective for the carbonylation of different aryl olefins and alcohols. Consecutive recycling and successful reuse proved the stability and true heterogeneous nature of all the anchored catalysts, which is a substantial advancement over the existing heterogeneous catalysts for carbonylation. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Anchored catalysts; Carbonylation; Immobilization; mesoporous materials; Palladium complex